К вопросу о границах сказуемого (на материале непроцессного квалификативного сказуемого в современном английском языке) - Драздаускас, А. (Kalbotyra, 1973)
The compound qualificative predicate (He is young, He is a doctor) often comprises different kinds of “complements”, for example: (1) “... You’re too young to understand” (A. Hall). (2) “He seems as vain as a peacock” (W. S. Maugham), etc.To understand the nature of the latter and what is most important to interpret them in terms of parts of the sentence the following method was used. If the “complement” is connected with the main part of the predicate by means of close attributive bond then it is regarded as a part of a part of a sentence and therefore as part of the compound predicate. When the bond is completive the “complement” is classified either as a prepositional: object or as an adverbial modifier. When defining the type of bond extensive use of different prosodic criteria is made.